2005
DOI: 10.1111/j.1474-7766.2005.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis and Treatment of Arteriovenous Malformations of the Brain

Abstract: INTRODUCTION Despite the passage of a century and a half since the first description of a brain arteriovenous malformation (AVM) (Rokitansky 1846), and although the imaging of brain AVMs advances relentlessly (Fig. 1), we still need adequate studies of brain AVM prognosis and reliable evaluations of their treatment. Prospective, population-based studies of brain AVM prognosis are underway (Al-Shahi et al. 2003; Stapf et al. 2003b), and a randomized controlledtrial (RCT) of their treatment is planned (http://w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…24 -30 In North America, suitable AVMs (such as Spetzler-Martin Grades I and II) seem to be excised more often than they are embolized, 2 but endovascular treatment (with or without radiosurgery) appears to have been used more frequently in Europe. 13 This study found minimal detectable heterogeneity between patients with AVMs evaluated at 4 neuroscience centers serving an entire population, but it detected differences in patterns of interventional AVM treatment and in particular differences between the 2 largest centers in the treatments used within the same Spetzler-Martin grade. Different patterns of interventional treatment may have arisen because of variation in the local availabilities of interventions, because of the lack of robust experimental evidence to inform our choice of whose AVM to treat and how 12 or for reasons that could not be assessed by this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…24 -30 In North America, suitable AVMs (such as Spetzler-Martin Grades I and II) seem to be excised more often than they are embolized, 2 but endovascular treatment (with or without radiosurgery) appears to have been used more frequently in Europe. 13 This study found minimal detectable heterogeneity between patients with AVMs evaluated at 4 neuroscience centers serving an entire population, but it detected differences in patterns of interventional AVM treatment and in particular differences between the 2 largest centers in the treatments used within the same Spetzler-Martin grade. Different patterns of interventional treatment may have arisen because of variation in the local availabilities of interventions, because of the lack of robust experimental evidence to inform our choice of whose AVM to treat and how 12 or for reasons that could not be assessed by this study.…”
Section: Discussionmentioning
confidence: 98%
“…2 Nevertheless, institutional, regional, national, and international variations in practice may exist, due to referral practices, selection for particular treatment modalities, availability of technical equipment, personal preference, and policies of health insurance systems, to name just a few reasons. 13 We sought to explore whether there were any detectable influences on regional patterns of AVM interventional treatment in one of the 2 ongoing, prospective, population-based cohort studies of AVM outcome. 3,4 …”
mentioning
confidence: 99%
“…Both interventional eradication and conservative follow-up are recognised management strategies in patients with brain arteriovenous malformations. 16,17 As far as we are aware, ARUBA is the first randomised controlled clinical trial assessing the outcomes from these two management strategies (ie, medical management with interventional therapy or medical management alone) in patients diagnosed with an unruptured brain arteriovenous malformation (panel). 18 …”
Section: Discussionmentioning
confidence: 99%
“…5 Because interventions may have complications 6 and the untreated clinical course of unruptured bAVMs can be benign, [1][2][3][4] some patients choose conservative management (without intervention). Unruptured bAVM intervention has been compared with conservative management in a concurrent control group in just 1 randomized trial (ARUBA) 7-9 and only a few observational studies, all of which have shown harm from intervention in the short term.…”
mentioning
confidence: 99%